Fostering better policy adoption and inter-disciplinary communication in healthcare: A qualitative analysis of practicing physicians’ common interests - Keller, Eric J. (PLoS One, 2017)
PURPOSE: In response to limited physician adoption of various healthcare initiatives, we sought to propose and assess a novel approach to policy development where one first characterizes diverse physician groups’ common interests, using a medical student and constructivist grounded theory. METHODS: In 6 months, a medical student completed 36 semi-structured interviews with interventional radiologists, gynecologists, and vascular surgeons that were systematically analyzed according to constructivist grounded theory to identifying common themes. Common drivers of clinical decision making and professional values across 3 distinct specialty groups were derived from physicians’ descriptions of their clinical decision making, stories, and concerns. RESULTS: Common drivers of clinical decision making included patient preference/benefit, experience, reimbursement, busyness/volume, and referral networks. Common values included honesty, trustworthiness, loyalty, humble service, compassion and perseverance, and practical wisdom. Although personal gains were perceived as important interests, such values were easily sacrificed for the good of patients or other non-financial interests. This balance was largely dependent on the incentives and security provided by physicians’ environments. CONCLUSIONS: Using a medical student interviewer and constructivist grounded theory is a feasible means of collecting rich qualitative data to guide policy development. Healthcare administrators and medical educators should consider incorporating this methodology early in policy development to anticipate how value differences between physician groups will influence their acceptance of policies and other broad healthcare initiatives.